Methane Adsorption Properties of Mn‐Modified Graphene: A First‐Principles Study. Issue 6 (28th April 2020) - Zhao, Yingjie; Chen, Yuhong; Song, Mingxia; Liu, Xiaocong; Xu, Wenhui; Zhang, Meiling; Zhang, Cairong
Abstract: Graphene (GR), as a 2D carbon nanomaterial with high specific surface area, is one of the primary candidates for energy‐storage applications. In this work, the adsorption properties of graphene and Mn‐modified graphene (Mn‐GR) systems for CH4 molecules are investigated, based on first‐principles density functional theory. It is found that intrinsic graphene adsorbs CH4 molecules weakly. The single side can adsorb up to 4 CH4 molecules, and the average adsorption energy is −0.220 eV per CH4 . Mn atom modification can significantly improve the adsorption performance of GR system on CH4 . The structure with the largest methane storage capacity is that the GR modified by two Mn atoms that are located in the spacer holes on the opposite sides. The system can adsorb 10 CH4 molecules on both sides, the CH4 adsorption amount can reach 32.93 wt%, and the average adsorption energy is −0.402 eV per CH4 . The interaction between the Mn atom and graphene is mainly between the d orbital of the Mn atom and the p orbital of the C atom. After the CH4 molecule is adsorbed, charge transfer occurs between Mn atoms and CH4, which results in a Coulomb attraction and enhances the adsorption performance of CH4 molecules. Abstract : Mn‐modified graphene improves methane adsorption performance. The interaction between the Mn atom and graphene is mainly between the d orbital of the Mn atom and the p orbital of the C atom. After a CH4 molecule is adsorbed, the coulomb attraction between Mn atom and CH4 is generated. The CH4 adsorption amount reaches 32.93 wt%.